Neoliberalism and punishment - González Sánchez, Ignacio (Routledge studies in crime & society, 2024)
"Exploring the expansion of the penal system in Spain during the first forty years of democracy, this book puts forward the importance of studying punishment from a sociological perspective and examines the neoliberal penalty thesis. Today, Spain has more police officers and more people in prison than fifty years ago, and a tougher penal code than that which existed at Franco's death; however, crime has not increased for three decades, while most of the hardening of the penal system has occurred after its stabilization. Studying the development of penality in Spanish democracy, this book explores Loïc Wacquant's proposal that the expansion of the penal system should be understood as a characteristic of neoliberalism. It examines the parallel and reciprocal development of three policies in relation to the gradual implementation of neoliberal ideas, and highlights how the evolution of the labour market, social policies, and the penal system are linked to one another, and to neoliberal ideas related to the sacralization of the utilitarian individual and the role of the state. Advocating for a sociological study of state punishment and contributing to a better understanding of the implementation of neoliberal policies, Neoliberalism and Punishment will be of great interest to students and scholars of criminology, sociology, and politics"--